A Cooperative Copper Metal–Organic Framework‐Hydrogel System Improves Wound Healing in Diabetes - Xiao, Jisheng; Chen, Siyu; Yi, Ji; Zhang, Hao F.; Ameer, Guillermo A. (Advanced functional materials, 2017)
Chronic nonhealing wounds remain a major clinical challenge that would benefit from the development of advanced, regenerative dressings that promote wound closure within a clinically relevant time frame. The use of copper ions has shown promise in wound healing applications, possibly by promoting angiogenesis. However, reported treatments that use copper ions require multiple applications of copper salts or oxides to the wound bed, exposing the patient to potentially toxic levels of copper ions and resulting in variable outcomes. Herein the authors set out to assess whether copper metal organic framework nanoparticles (HKUST‐1 NPs) embedded within an antioxidant thermoresponsive citrate‐based hydrogel would decrease copper ion toxicity and accelerate wound healing in diabetic mice. HKUST‐1 and poly‐(polyethyleneglycol citrate‐co‐N‐isopropylacrylamide) (PPCN) are synthesized and characterized. HKUST‐1 NP stability in a protein solution with and without embedding them in PPCN hydrogel is determined. Copper ion release, cytotoxicity, apoptosis, and in vitro migration processes are measured. Wound closure rates and wound blood perfusion are assessed in vivo using the splinted excisional dermal wound diabetic mouse model. HKUST‐1 NPs disintegrated in protein solution while HKUST‐1 NPs embedded in PPCN (H‐HKUST‐1) are protected from degradation and copper ions are slowly released. Cytotoxicity and apoptosis due to copper ion release are significantly reduced while dermal cell migration in vitro and wound closure rates in vivo are significantly enhanced. In vivo, H‐HKUST‐1 induced angiogenesis, collagen deposition, and re‐epithelialization during wound healing in diabetic mice. These results suggest that a cooperatively stabilized, copper ion‐releasing H‐HKUST‐1 hydrogel is a promising innovative dressing for the treatment of chronic wounds. A copper ion‐eluting thermoresponsive antioxidant hydrogel consisting of metal organic framework (HKUST‐1) nanoparticles and poly(polyethylene glycol citrate‐co‐N‐isopropylacrylamide) is prepared and characterized (H‐HKUST‐1). H‐HKUST‐1 exhibits significantly reduced cytotoxicity and promotes the migration of dermal cells in vitro. In vivo, H‐HKUST‐1 promotes improved dermal wound closure rates in diabetic mice.